Utilization Effect of Sardinella lemuru Fish Oil and Sprouted Mung Bean (Vigna radiata) on Broiler Performance and Income Over Feed Cost - H. Djunaidi, Irfan; Ampode, Kremlin Mark B. (CV. Komunitas Dunia Peternakan, 2024)
The research was aimed to evaluate the effect of addition Sardinella lemuru oil (SLO) and sprouted mung bean (SMB) supplementation on performance broiler and IOFC. The material used in this research were 160 unsexed Cobb Strain DOC broiler. The method used Completely Randomized Design with 4 treatments and 5 replications, and the experiment tested T0 (basal feed) as a control, T1(basal feed + SMB 0.5% + SLO 1.5%), T2 (basal feed +SMB 0.5% + SLO 3%), T3 (basal feed + SMB 0.5% + SLO 4.5%) as feed given. Variable measured were feed consumption, body weight gain, feed conversion, index of production, and income over feed cost. The data collected and analysed using Variance analysis and the Duncan Multiple Range Test further tested any significant difference. The results were showed that the addition of Sardinella lemuru oil 4.5% and sprouted mung bean 0.5% highly significant (P<0.01) affected feed consumption, feed conversion, body weight gain, income over feed cost and no significant effected on the index of production.